The Radiological Spectrum of Orbital Pathologies that Involve the Lacrimal Gland and the Lacrimal Fossa - Jung, Won Sang; Ahn, Kook Jin; Park, Mi Ra; Kim, Ji Young; Choi, Jae Jeong; Kim, Bum Soo; Hahn, Seong Tai (Korean journal of radiology, 2007)
CT and MRI are utilized to differentiate between different types of masses and to determine the extent of lesions involving the lacrimal gland and the fossa. Although many diseases that affect the lacrimal gland and fossa are specifically diagnosed by imaging, it is frequently very difficult to differentiate each specific disease on the basis of image characteristics alone due to intrinsic similarities. In lacrimal gland epithelial tumors, benign pleomorphic adenomas are seen most commonly with a well defined benign appearance, and a malignant adenoid cystic carcinoma is seen with a typical invasive malignant appearance. However, a malignant myoepithelial carcinoma is seen with a benign looking appearance. Lymphomatous lesions of the lacrimal gland include a broad spectrum ranging from reactive hyperplasia to malignant lymphoma. These lesions can be very difficult to differentiate both radiologically and pathologically. Generally, lymphomas tend to occur in older patients. The developmental cystic lesions found in the lacrimal fossa such as dermoid and epidermoid cysts can be diagnosed when the cyst involves the superior temporal quadrant of the orbit and manifests as a non-enhancing cystic mass and, in case of a lipoma, it is diagnosed as a total fatty mass. However, masses of granulocytic sarcoma and xanthogranuloma, as well as vascular masses, such as a hemangiopericytoma, are difficult to diagnose correctly on the basis of preoperative imaging findings alone. A careful clinical evaluation and moreover, a pathologic verification, are needed. In this pictorial review, the various imaging spectrums of pathologic masses involving the lacrimal gland and fossa are presented, along with appropriate anatomy and pathology reviews.